MotionCLIP: Exposing Human Motion Generation to CLIP Space - Tevet, Guy; Gordon, Brian; Hertz, Amir; Bermano, Amit H.; Cohen-Or, Daniel (Computer Vision - ECCV 2022, 2022)
We introduce MotionCLIP, a 3D human motion auto-encoder featuring a latent embedding that is disentangled, well behaved, and supports highly semantic textual descriptions. MotionCLIP gains its unique power by aligning its latent space with that of the Contrastive Language-Image Pre-training (CLIP) model. Aligning the human motion manifold to CLIP space implicitly infuses the extremely rich semantic knowledge of CLIP into the manifold. In particular, it helps continuity by placing semantically similar motions close to one another, and disentanglement, which is inherited from the CLIP-space structure. MotionCLIP comprises a transformer-based motion auto-encoder, trained to reconstruct motion while being aligned to its text label’s position in CLIP-space. We further leverage CLIP’s unique visual understanding and inject an even stronger signal through aligning motion to rendered frames in a self-supervised manner. We show that although CLIP has never seen the motion domain, MotionCLIP offers unprecedented text-to-motion abilities, allowing out-of-domain actions, disentangled editing, and abstract language specification. For example, the text prompt “couch” is decoded into a sitting down motion, due to lingual similarity, and the prompt “Spiderman” results in a web-swinging-like solution that is far from seen during training. In addition, we show how the introduced latent space can be leveraged for motion interpolation, editing and recognition (See our project page: https://guytevet.github.io/motionclip-page/.